In support of teacher transformation: emotions as pedagogy - Jude Walker (Adult Education Research Conference, 2018)
This paper explores the role of emotions in the classroom as a form of pedagogy for potential transformative learning of the adult educator.
Keywords: emotion; teachers; courage